Affording autism an early brain development re-definition. (October 2020) - Klin, Ami; Micheletti, Megan; Klaiman, Cheryl; Shultz, Sarah; Constantino, John N.; Jones, Warren
Abstract: The national priority to advance early detection and intervention for children with autism spectrum disorder (ASD) has not reduced the late age of ASD diagnosis in the US over several consecutive Centers for Disease Control and Prevention (CDC) surveillance cohorts, with traditionally under-served populations accessing diagnosis later still. In this review, we explore a potential perceptual barrier to this enterprise which views ASD in terms that are contradicted by current science, and which may have its origins in the current definition of the condition and in its historical associations. To address this perceptual barrier, we propose a re-definition of ASD in early brain development terms, with a view to revisit the world of opportunities afforded by current science to optimize children's outcomes despite the risks that they are born with. This view is presented here to counter outdated notions that potentially devastating disability is determined the moment a child is born, and that these burdens are inevitable, with opportunities for improvement being constrained to only alleviation of symptoms or limited improvements in adaptive skills. The impetus for this piece is the concern that such views of complex neurodevelopmental conditions, such as ASD, can become self-fulfilling science and policy, in ways that are diametrically opposed to what we currently know, and are learning every day, of how genetic risk becomes, or not, instantiated as lifetime disabilities.